Dark Times Are Over? - Obafemi, Olu (University Press Plc, 2008)
Dark Times Are Over? satirizes the decay in the university system and the large society:prostitution,cultism,religious zealotry and injustice.
Keywords: Drama; Injustice; Nigeria(English); Society